Factors of professional burnout in social workers who work with elderly people - Sadrytska, Svitlana; Selevko, Maryna (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2024)
The article examines one of the relevant problems for social work – professional burnout of specialists. Attention is focused on the impact of a complex of factors that are intensified by the work of social workers in wartime conditions. The authors pay main attention to the peculiarities of working with elderly people, which in their opinion significantly affect the professional burnout of social workers, as they require both physical and significant emotional and psychological resources. The authors analyze the age boundaries of old age, based on biological, social and demographic indicators. Age-specific characteristics of old age are considered: main tasks, influence of basic social institutions, possible risks and dangers. The article notes the specifics of elderly people as clients of social work, emphasizing the tendency to increase the number of such clients due to demographic and socio-economic factors. The intensification of burnout manifestations under the influence of such factors as emotional exhaustion, physical fatigue, psychological pressure, negative impact of the client’s personal stories, insufficient recognition and support from society are analyzed. The authors propose organizational measures to prevent burnout of social workers, taking into account the characteristics of elderly clients: regulation of time expenditures, encouragement and support of the professional environment, information work in the community, attention of management and others. The article concludes that professional burnout among social workers who work with the elderly is caused by a complex interaction of emotional, physical, social and organizational factors. Avoiding this syndrome requires comprehensive support, improving work organization, implementing emotional self-regulation strategies, taking into account the specifics of working with elderly people in measures aimed at preventing and overcoming professional burnout of social workers.